Batu city bawaslu strategy in preventing political money in the 2024 election - Wibowo, Arif Prasetyo; Yusril Abdillah, Achmad; Widodo, Rohmad (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2024)
The aim of this research is to broaden understanding in political education and expand knowledge in Pancasila and citizenship education. Because Indonesia is a country that adheres to a democratic system which is carried out through elections and regional elections, the main aim of the research is how to find out problems in elections, namely money politics which is used as a tool in winning contestations. And what is the role and response of the community to money politics, as well as to find out regulatory weaknesses that cause weak election law enforcement. The method used in this research uses descriptive qualitative and legal and regulatory instruments to strengthen credible data, and obtains data through interviews with Batu City Bawaslu commissioners. The results prove that society is very indifferent to electoral developments and problems, as well as the weakness of applicable laws and regulations. Bawaslu increases participatory supervision to maintain the quality of democracy